TINJAUAN FIKIH MUNAKAHAT DALAM BUDAYA MERARIK SUKU SASAK DI LOMBOK TIMUR - Saidi, Abdul Gafar; Rifai, Muhammad Agus; Parhi, Nurmu'izzatin Zaharatul (Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2024)
Marriage in Islam has a religious meaning that is very high in value and important in human life, because marriage is a form of basic human needs, also included in the holy agreement between men and women. The purpose of this research is to find out the reasons why people still carry out the Merarik custom. This type of research is normative empirical legal research, the data sources needed in this research are divided into two sources, namely primary and secondary data sources, while data collection techniques use document studies and interviews. The data analysis in this research uses qualitative descriptive analysis. The results of this study explain that in the tradition of the Lombok people a proposal is replaced by the term Merarik, this is a hereditary tradition besides being done by proposing. The memaling tradition in Merarik is carried out as a form of society still holding customs that show the masculinity of a man rather than proposing directly which sometimes in the Sasak community it is a form of demeaning the parents of women.